2011
DOI: 10.15292/geodetski-vestnik.2011.01.011-027
|View full text |Cite
|
Sign up to set email alerts
|

Automatic extraction and building change detection from digital surface model and multispectral orthophoto

Abstract: IZVLEČEK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 3 publications
(3 reference statements)
1
21
0
Order By: Relevance
“…A detailed explanation of this phase is omitted from this article for issues of length, but a complete description can be found in a previous paper . A literature review revealed the concern that use of the NDVI for the elimination of vegetation from further data processing steps carries the risk that the shadowed parts of the buildings will also be eliminated from the processing [Grigillo et al, 2011]. For this reason, the same procedure was used to classify the shadows in the image.…”
Section: Ndvi Nir Vis Nir Vismentioning
confidence: 99%
“…A detailed explanation of this phase is omitted from this article for issues of length, but a complete description can be found in a previous paper . A literature review revealed the concern that use of the NDVI for the elimination of vegetation from further data processing steps carries the risk that the shadowed parts of the buildings will also be eliminated from the processing [Grigillo et al, 2011]. For this reason, the same procedure was used to classify the shadows in the image.…”
Section: Ndvi Nir Vis Nir Vismentioning
confidence: 99%
“…Lee et al, 2003, Cha et al, 2006, Koc San and Turker, 2010. The similar approach employing Radon transform is described in Grigillo et al (2011).…”
Section: References To Related Workmentioning
confidence: 99%
“…Additionally we used building outlines image. The elaboration of mask for the building area test and the building outlines image is in detail discussed in Grigillo et al (2011) within section 3.3. The mask for the building area test is made with a series of morphological operations from the initial building mask.…”
Section: Automatic Building Extractionmentioning
confidence: 99%
“…Automatic building change detection from remote sensing data mainly falls into two categories (Grigillo et al, 2011). Firstly, in the direct approach, data acquired from one type of sensor at two different dates are directly compared to detect changes.…”
Section: Introductionmentioning
confidence: 99%